Exceeding 30% Efficiency of Red Perovskite Quantum Dot Light-Emitting Diodes via Interparticle Energy Dissipation Suppression - Yao, Zhiwei; Liang, Changsheng; Bi, Chenghao; Zhou, Wenyuan; Ren, Ke; Deng, Ming; Ding, Shuo; Xiang, Chaoyu (Nano-Micro Letters, 2026)
The performance limits of perovskite quantum dot (QD) light-emitting diodes (PeLEDs) remain incompletely explored currently. Energy dissipation arising from interdot electronic coupling in QD solid films is readily induced by reduced interparticle distances and delocalized electron wavefunctions, thereby triggering severe nonradiative recombination and impeding further efficiency gains. To mitigate this energy loss, 1H,1H-undecafluorohexylamine (11-PFHA), characterized by pronounced steric self-repulsion and concentrated electron density distribution, was employed. The steric self-repulsion of 11-PFHA enlarges interdot spacing, while its concentrated electron distribution restructures the QDs’ surface electron distribution and establishes a higher interfacial electronic potential barrier between adjacent QDs. The treatment of 11-PFHA effectively suppresses electronic coupling and concomitant energy dissipation. Consequently, 11-PFHA-treated red-emitting perovskite QDs exhibit a near-unity photoluminescence quantum yield. PeLEDs fabricated with these optimized QDs achieve record external quantum efficiencies (EQEs), reaching 28.9% at 640 nm and 32.0% at 657 nm, indicating the highest EQE values reported to date. Highlights: 1 A new quantum dot (QD) films with negligible redshift of photoluminescence spectra after film fabrication from QD solution. 2 An electron barrier around QDs realized by adopting ligands with concentrated electron distribution. 3 Record external quantum efficiency of light-emitting diodes based on CsPbI3 QDs (28.9% at 640 nm and 32.0% at 657 nm).